2002
DOI: 10.1029/2001wr001204
|View full text |Cite
|
Sign up to set email alerts
|

A geostatistically based inverse model for electrical resistivity surveys and its applications to vadose zone hydrology

Abstract: [1] A sequential, geostatistical inverse approach was developed for electrical resistivity tomography (ERT). Unlike most ERT inverse approaches, this new approach allows inclusion of our prior knowledge of general geological structures of an area and point electrical resistivity measurements to constrain the estimate of the electrical resistivity field. This approach also permits sequential inclusion of different data sets, mimicking the ERT data collection scheme commonly employed in the field survey. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 35 publications
1
101
0
Order By: Relevance
“…Weakly nonlinear problems can be solved with an iterative procedure that solves the cokriging equations at each iteration [Yeh et al, 1996] and applications to geophysics have been reported [Yeh et al, 2002].…”
Section: Formulation Of the Inverse Problemmentioning
confidence: 99%
“…Weakly nonlinear problems can be solved with an iterative procedure that solves the cokriging equations at each iteration [Yeh et al, 1996] and applications to geophysics have been reported [Yeh et al, 2002].…”
Section: Formulation Of the Inverse Problemmentioning
confidence: 99%
“…The relative inexpensiveness of the sensor makes such a deployment feasible, thus making ERT a highly desirable monitor tool for vadose zone investigations. Nonetheless, a recent field study (Baker, 2001 andYeh et al, 2002) indicated that the parameters of Arche's law (i.e., the resistivity/moisture content relation) exhibit profound spatial variability. This variability compounds the difficulty in translating resistivity to moisture content.…”
Section: Electrical Resistivity Tomography For Monitoring the Vadose mentioning
confidence: 99%
“…For large -scale investigations, recently developed geophysical methods (such as electrical resistivity tomography, ERT; ground penetrating radars, GPR; Binley et al, 2001. Daily et al, 1992 for characterizing and monitoring the vadose zone, coupled with geostatistically based inverse methods Yeh et al, 2002) appear to be promising.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, data fusion techniques have been developed for coupled inversion of multiplesource data to estimate K distributions for groundwater numerical modeling. Geophysical data (such as surface electric resistivity and various logging data) are relatively inexpensive and can provide considerable information for characterizing subsurface heterogeneous properties (Hubbard et al, 2001;Yeh et al, 2002;Dai et al, 2004a;Morin, 2006;Sikandar et al, 2010;Bevington et al, 2016). Electric resistivity data have been proven useful to derive sediment porosity distributions (Niwas and Singhal, 1985;Niwas et al, 2011;Niwas and Celik, 2012;Zhu et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%